2014
DOI: 10.14260/jemds/2014/4092
|View full text |Cite
|
Sign up to set email alerts
|

A MORPHOMETRIC STUDY OF ATLAS & AXIS VERTEBRAE IN RAJASTHAN POPULATION

Abstract: Knowing the dimensions of the vertebral elements is very important for the development of instrumentation related to cervical spine. Ethnic variations have been reported in these dimensions. Aim of the present study was to evaluate the metrical details of first and second cervical vertebrae to correct the instability of atlantoaxial joint, and to analyze the morphological features to understand the ergonomics of the craniovertebral joints. This study was conducted in the Department of Anatomy S. M. S. Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 6 publications
5
4
1
Order By: Relevance
“…Bazaldua et al ( 30 ), studied the morphometry of the cervical vertebrae C3-7 in a population from Northeastern Mexico and measured the distance from the superior border to the tip of the SP in the sagittal plane to determine a mean value of 29.12±5.86 mm, which was in accordance with the results of the present study. However other studies obtained measures of 22.19±2.02 and 22.78±2.03 mm ( 31 , 32 ), which was smaller than the result of the present study. These discrepancies may be the result of the various measuring criteria, inter-regional or -ethnic differences and statistical errors.…”
Section: Discussioncontrasting
confidence: 99%
“…Bazaldua et al ( 30 ), studied the morphometry of the cervical vertebrae C3-7 in a population from Northeastern Mexico and measured the distance from the superior border to the tip of the SP in the sagittal plane to determine a mean value of 29.12±5.86 mm, which was in accordance with the results of the present study. However other studies obtained measures of 22.19±2.02 and 22.78±2.03 mm ( 31 , 32 ), which was smaller than the result of the present study. These discrepancies may be the result of the various measuring criteria, inter-regional or -ethnic differences and statistical errors.…”
Section: Discussioncontrasting
confidence: 99%
“…Although in case of spinal canal depth, Sengul measured values considerably greater than other studies. However, Singla, Gosavi and Xu presented the parameters very similar to the present study [18,26,27]. …”
Section: Resultssupporting
confidence: 85%
“…Although the width is mostly bigger than the depth, values do not differ significantly and for specimen 2 and 3 they are almost the same. Vertebral body measurement including vertebral body length, width, anterior and posterior height was previously performed by Gosavi [26], Singla [27], Naderi [11], Xu [18] and Dohery [24]. In Figure 4, the comparison to the present study is shown.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations